PERAN UNICEF DALAM MENGATASI PELANGGARAN PEKERJA ANAK DI INDIA PADA TAHUN 2018-2020 - Jovita Karen Sunarti Coulter, (2022)
This study aims to determine UNICEF's efforts to address child labor violations in India in 2018-2020 where the level of child labor in India is very high with the main cause being poverty. Other factors contributing to the high rate of child labor in India are environmental, social and low levels of education. Types of child labor in India are very dangerous for child development, for example children work in glass making, garments, tea plantations, prostitution, and others. UNICEF is an international organization whose main goal is to fight for children's rights. So it is very appropriate to cooperate with UNICEF to solve the problem of child labor in India. But UNICEF still has to work with India to launch its programs. The theories used in this research are human security, child labor, human rights, and international organizations. These theories are very important to analyze cases of child labor violations in India that are related to human security and human rights violations and their resolution is assisted by international organizations. In this study, the focus is more on analyzing descriptively how UNICEF's efforts in overcoming child labor in India. UNICEF has many universal programs which India then implements these programs with the help of UNICEF until it is quite effective in reducing child labor in India.